Cyber Security Protection of Power System Equipment Based on Chip-Level Trusted Computing - Xi, Wei; Li, Xiaobo; Feng, Qihui; Yao, Hao; Cai, Tiantian; Yu, Yang (Frontiers in Energy Research, 2022)
This paper proposes a network security protection scheme for power system embedded devices based on chip-level trusted computing, gives the overall architecture of power equipment chip-level trusted computing, introduces the principle of trust chain transfer within power terminals, and proposes the method of using the on-chip SRAM inside the main control chip of power system embedded devices as the PUF to construct the trusted root. Furthermore, we propose a complete trust transfer mechanism from booting trust to the loading that trust on operating system and application, and give the corresponding program design framework and Program logic. The chip-level trusted computing program designed in this paper was applied in a distribution automation DTU device equipped with the FUXI chip that is developed by China Southern Power Grid and the Sylix OS operating system. Finally, we carry out the security protection test. By running malicious programs, the Mirai virus attack to verify the effectiveness of the designed program for the detection and interception of illegal programs, and provides a set of effective solutions for the security protection of power system terminal equipment in an open network environment.